Financial incentives and purchase restrictions in a food benefit program affect the types of foods and beverages purchased: results from a randomized trial - Simone A. French; Sarah A. Rydell; Nathan R. Mitchell; J. Michael Oakes; Brian Elbel; Lisa Harnack (BMC, 2017)
Abstract Background This research evaluated the effects of financial incentives and purchase restrictions on food purchasing in a food benefit program for low income people. Methods Participants (n=279) were randomized to groups: 1) Incentive- 30% financial incentive for fruits and vegetables purchased with food benefits; 2) Restriction- no purchase of sugar-sweetened beverages, sweet baked goods, or candies with food benefits; 3) Incentive plus Restriction; or 4) Control- no incentive or restrictions. Participants received a study-specific debit card where funds were added monthly for 12-weeks. Food purchase receipts were collected over 16 weeks. Total dollars spent on grocery purchases and by targeted food categories were computed from receipts. Group differences were examined using general linear models. Results Weekly purchases of fruit significantly increased in the Incentive plus Restriction ($4.8) compared to the Restriction ($1.7) and Control ($2.1) groups (p <.01). Sugar-sweetened beverage purchases significantly decreased in the Incentive plus Restriction (−$0.8 per week) and Restriction ($-1.4 per week) groups compared to the Control group (+$1.5; p< .0001). Sweet baked goods purchases significantly decreased in the Restriction (−$0.70 per week) compared to the Control group (+$0.82 per week; p < .01). Conclusions Paired financial incentives and restrictions on foods and beverages purchased with food program funds may support more healthful food purchases compared to no incentives or restrictions. Clinical trial registration Clinicaltrials.gov Identifier: NCT02643576 .